Viola canina × uliginosa herbārijs no Moricsalas - Lackschewitz, Paul (My University, 1909)
Paula Lakševica (Lackschewitz; 1865 – 1936) Moricsalā ievāktais vijolītes Viola canina × uliginosa herbārijs glabājas Herbarium Latvicum (RIG II) kolekcijā Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekcijās. Herbārijs ir ievākts, veicot sākotnējo salas floras izpēti, kurā piedalījās vairāki Baltijas dabaspētnieki. Izpētes rezultāti kalpoja par pamatu, Moricsalas dabas rezervāta izveidei.

Paul Lackschewitz’s (1865 – 1936) collected herbarium of the violet Viola canina × uliginosa in Moricsala is stored in the Herbarium Latvicum (RIG II) collection in the Botany and Mycology collections of the Museum of the University of Latvia . The herbarium was collected during the preliminary study of the flora of the island, in which several Baltic naturalists participated. The research results served as the basis for the creation of the Moricsala Strict Nature Reserve
Herbarium of Viola canina × uliginosa from Moritcsala
Keywords: Moricsala; Viola canina × uliginosa; vijolīte; violet; Pauls Lakševics; Herbarium Latvicum; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology